2005
DOI: 10.1093/nar/gki725
|View full text |Cite
|
Sign up to set email alerts
|

Structural and DNA-binding studies on the bovine antimicrobial peptide, indolicidin: evidence for multiple conformations involved in binding to membranes and DNA

Abstract: Indolicidin, a l3-residue antimicrobial peptide-amide, which is unusually rich in tryptophan and proline, is isolated from the cytoplasmic granules of bovine neutrophils. In this study, the structures of indolicidin in 50% D3-trifluoroethanol and in the absence and presence of SDS and D38-dodecylphosphocholine were determined using NMR spectroscopy. Multiple conformations were found and were shown to be due to different combinations of contact between the two WPW motifs. Although indolicidin is bactericidal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
203
2
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(236 citation statements)
references
References 45 publications
19
203
2
5
Order By: Relevance
“…AMPs comprise part of the innate immune system of many organisms and help protect the host species from microbial invasion/infection. Current dogma dictates that the antimicrobial activity of these peptides is mediated through interaction of AMPs with target cell membranes and subsequent membrane disruption, although other mechanisms have been postulated [12][13][14]. The current study expands on previous work developing AMP-based detection assays for Escherichia coli and Salmonella typhimurium [15,16].…”
Section: Introductionmentioning
confidence: 77%
“…AMPs comprise part of the innate immune system of many organisms and help protect the host species from microbial invasion/infection. Current dogma dictates that the antimicrobial activity of these peptides is mediated through interaction of AMPs with target cell membranes and subsequent membrane disruption, although other mechanisms have been postulated [12][13][14]. The current study expands on previous work developing AMP-based detection assays for Escherichia coli and Salmonella typhimurium [15,16].…”
Section: Introductionmentioning
confidence: 77%
“…Buforin II was previously found to bind pDNA at a weight ratio of above 1:0.25 (pDNA:peptide) [23]. Another AMP, indolicidin, has been shown to cause membrane permeabilization without cell lysis, and to have possible intracellular targets through which it kills bacteria [13]. Indolicidin retards the movement of DNA at pDNA:peptide ratios of above 1:0.2 [13].…”
Section: Discussionmentioning
confidence: 99%
“…Another AMP, indolicidin, has been shown to cause membrane permeabilization without cell lysis, and to have possible intracellular targets through which it kills bacteria [13]. Indolicidin retards the movement of DNA at pDNA:peptide ratios of above 1:0.2 [13]. The peptides Os and Os-C cause pDNA retardation at weight ratios above 1:1.2 and 1:1 (pDNA:peptide), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The actual contact between an AMP and DNA was demonstrated with indolicidin, a potent cationic peptide that enters bacterial cells without causing lysis and inhibits DNA replication [61]. These experiments showed that indolicidin assumes different environmentdependent conformations and prefers to bind certain sequences of double stranded DNA and that it binds poorly to single stranded DNA .…”
Section: Cationic Peptide Interaction With Nucleic Acidsmentioning
confidence: 99%